Effects of Different Fatty Acids as Surfactants on the Rheological Properties of Kerosene-Based Magnetic Fluids - Zang, Guobao; Zhang, Zhili; Yu, Wenjuan; Wang, Deyi; Li, Decai (Frontiers in Materials, 2022)
Three types of surfactants (oleic acid, linoleic acid, and a mixture of oleic acid and linoleic acid) were coated on ferromagnetic particles, which were dispersed in kerosene to prepare magnetic fluids, to study the effect of different fatty acids as surfactants on the rheological properties of magnetic fluids. The particles were analyzed by XRD, TEM, FT-IR, and VSM. Furthermore, a rheometer was used to examine the rheological properties of kerosene-based magnetic fluids dispersed with various surfactants. The yield stress at different magnetic fields was calculated by fitting the Herschel–Bulkley model. The fitted curve and the observed values of mixed fatty acids are identical. The graphs of viscosity increase with the shear rate for each magnetic fluid were measured at constant magnetic field strengths. At constant shear rates, the curves of viscosity increase with magnetic field intensity were measured. In the absence of a magnetic field, the relative change in viscosity from 40°C to 0°C was observed. The rheological measurements of the mixed fatty acid-dispersed ferrofluid with a rising magnetic field at a constant shear rate are smoother than the single-fatty-acid-dispersed ferrofluid, indicating that it is more stable. As the temperature is dropped, the viscosity–temperature curve evidence that mixed fatty acids as surfactants can lower the proportion of magnetic fluid viscosity rise.